2018
DOI: 10.3390/su10114099
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Agriculture Using Coulters: Effects of Crop Residue on Working Performance

Abstract: Conservation agriculture is an important measure promoting sustainable agriculture in northeast China. Coulters in the conservation agriculture system are used to cut the excessive residue in strips, loosen soils, and create good seedbeds. Information on the performance of coulters worked in a field with or without corn residue coverage is lacking in the literature. In this study, five coulters were tested in two field conditions at three working velocities to compare their performance. The five coulters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Table 5 showed that the "Pred R-Squared" of 0.9601 was in reasonable agreement with the "Adj R-Squared" of 0.9792 ( Table 5). The final regression model was given in Equation 2: SCR = −20.827 + 0.3338 × P + 1.589 × α − 2.4925 × v − 2.9292 × 10 -3 × P × α − 4.4147 × 10 -3 ×α 2 (2) where, SCR is stalks cutoff ratio, %; P is the waterjet pressure, MPa; α is the jet impingement angle, (°); v is the forward speed of waterjet, km/h. The value of SCR increased with increasing P and α, and decreased with increasing v. It was mainly caused by the cutting principle of waterjet.…”
Section: Effects Of Operation Parameters On Scr and Dscmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 showed that the "Pred R-Squared" of 0.9601 was in reasonable agreement with the "Adj R-Squared" of 0.9792 ( Table 5). The final regression model was given in Equation 2: SCR = −20.827 + 0.3338 × P + 1.589 × α − 2.4925 × v − 2.9292 × 10 -3 × P × α − 4.4147 × 10 -3 ×α 2 (2) where, SCR is stalks cutoff ratio, %; P is the waterjet pressure, MPa; α is the jet impingement angle, (°); v is the forward speed of waterjet, km/h. The value of SCR increased with increasing P and α, and decreased with increasing v. It was mainly caused by the cutting principle of waterjet.…”
Section: Effects Of Operation Parameters On Scr and Dscmentioning
confidence: 99%
“…Conservation agriculture plays an important role of sustainable agriculture and soil protection. No-till seeders or planters are intended to working in the field with straw cover, and place seed and fertilizer at the certain depth precisely [1][2][3] . Even though with these sustainable and climate smart advantages, it encounters the problem that when seeding on a no-till field, crop stalks and residue often wind around furrow openers or seeding devices, which makes the no-till seeder cannot work stably.…”
Section: Introduction mentioning
confidence: 99%
“…Conversely, leaving the crop residue of the soil surface can reduce the sowing quality or complicating sowing operations through blockage of furrowing and seeding devices, reducing soil temperature and consequently interfere with the rate and time of seed emergence (Wang et al, 2018). Younis et al (2020b) used the modification of row cleaner for zero tillage planter to clean the seeding row from the residue by adding a halfcylindrical plate to cover the stem of furrow openers.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large amount maize stalks/residue is relatively fresh and hard to cut following the maize harvest. This poses a dilemma in the summer maize and winter wheat cropping system, such that large amounts of maize residue could cause plugging of furrow openers and metering devices [7] .…”
Section: Introductionmentioning
confidence: 99%